Lesson studies in initial mathematics teacher education - Ponte, João Pedro da (2017)
Purpose – The purpose of this paper is to review the research concerning the use of lesson studies in the education of secondary school prospective mathematics teachers. It discusses the adaptations made on the designs, the aims and outcomes established, the processes used, and the needed improvements in the experiences reported so far. Design/methodology/approach – The scientific studies reviewed were identified in a Google search, using the key words “lesson study”, “mathematics”, and “secondary.” The identified material was recorded in a database and the themes for the analysis cover the planning, execution, and reflection phases of a formative process. Findings – The paper identifies the several pending issues regarding the use of lesson studies in prospective teacher education such as defining the aims, establishing the relationships among participants, scaling, and adapting lesson studies for the particular purpose of educating future teachers. Research limitations/implications – At a practical level, this review suggests that lesson studies in pre-service teacher education must have a clear formative aim. It also shows that many formats are possible and must be chosen according to the specific conditions. In addition, it suggests the need for research regarding the definition of the aims, the working relationships established among participants, the problem of scale, and the problem of adaptation or simplification. Originality/value – The paper identifies the key issues in the design of lesson studies in initial teacher education. It argues that besides signaling the positive outcomes, more critical (or self-critical) investigations are needed, e.g. using external researchers as “critical friends”, which address their difficulties, limitations, and drawbacks in a more thorough way.